Perjanjian Waralaba yang Belum Terdaftar: Batal Demi Hukum atau Dapat Dibatalkan? - Rahma Widiastuti, Ambria; Akhmad Budi Cahyono (Universitas Ekasakti, 2024)
Government Regulation Number 42 of 2007 concerning Franchising (PP 42/2007), requires that the Franchisor must register the Franchise prospectus which is followed up with the registration of the Franchise Agreement by the Franchisee. Failure to register the Franchise Agreement results in the agreement being null and void because the Franchise Agreement is included in the form of a Formal Agreement. Void and void means returning the parties to their original state when the agreement had not yet been formed. However, if the Franchisee suffers a loss, he can sue the Franchisor for compensation on the basis of an Unlawful Act. The Franchisee will not experience such losses if the Franchisor registers its franchise prospectus. This study uses a normative legal research method with a qualitative approach.